2005
DOI: 10.1002/sia.1971
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of Co thin films grown on Ge(111) at room temperature by x‐ray photoelectron diffraction

Abstract: The thickness dependence of the structure of ultrathin Co films grown on Ge(111), using molecular beam epitaxy at room temperature, was studied via low energy-electron diffraction (LEED) and x-ray photoelectron diffraction. Cobalt deposition led to a surface phase transition from a c(2 × 8) reconstruction to a (1 × 1) structure. The (1 × 1) LEED pattern was gradually degraded with increased Co coverages, implying partial loss of long-range order. Experimental and theoretical XPED studies revealed that 0.7 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Deviation from this can occur for the thin lm deposited at low deposition rates, especially at elevated substrate temperatures, as observed in the Co-Ge and Co-Si system where Ge-or Si-rich germanides are formed rst. 48,49 Similar to our ndings, Mello et al 20 have reported in their studies, using a partially ionized beam technique, the direct formation of CoGe 2 on GaAs substrates, independent of the applied ion energy. In our present study, since the direct formation of CoGe 2 lms is observed at very low temperatures, it is very probable that the faster consumption of Ge from GeH 4 precursors results in a different cobalt germanide formation mechanism.…”
Section: Resultssupporting
confidence: 87%
“…Deviation from this can occur for the thin lm deposited at low deposition rates, especially at elevated substrate temperatures, as observed in the Co-Ge and Co-Si system where Ge-or Si-rich germanides are formed rst. 48,49 Similar to our ndings, Mello et al 20 have reported in their studies, using a partially ionized beam technique, the direct formation of CoGe 2 on GaAs substrates, independent of the applied ion energy. In our present study, since the direct formation of CoGe 2 lms is observed at very low temperatures, it is very probable that the faster consumption of Ge from GeH 4 precursors results in a different cobalt germanide formation mechanism.…”
Section: Resultssupporting
confidence: 87%
“…A way to accomplish control over these key parameters is to use the lattice misfit between substrate and nanostructure. Recent studies have revealed that the deposition of metals such as Pt [1], Au [2][3][4], and Co on semiconductor group IV (001) surfaces [5][6][7][8][9][10][11][12][13][14] leads to a plethora of novel nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…For Co–Si, the atomic environment of a Co atom embedded in a cluster with three adatoms is very close to that of a Co atom located at the interface between a CoSi 2 island (with fluorite structure) and a Si(111) surface . In contrast, the thermodynamically favoured CoGe 2 phase that forms even at room temperature for higher Co coverages exhibits an orthorhombic structure . Thus, the atomic arrangement of a 13 cluster comprising three adatoms is quite different from that of CoGe 2 .…”
Section: Resultsmentioning
confidence: 96%
“…After annealing at about 870 K, epitaxial CoSi 2 films are formed on Si(111) . In contrast, for a deposition at room temperature on the Ge(111)– c (2 × 8), the resulting layer is mainly composed of the CoGe 2 phase with an orthorhombic structure ( a = b = 0.567 nm, c = 1.0796 nm), at least up to a 1.5 ML coverage . Thus, it is of crucial importance to study the reorganization of the Co–Si and Co–Ge interfaces upon Co deposition and eventually annealing of the system.…”
Section: Introductionmentioning
confidence: 99%